Adsorption of copper and cadmium ions by activated carbon from rice hulls - Teker, M; Imamoglu, M; Saltabas, Ö (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY, 1999)
The removal of copper (II) and cadmium (II) ions from aqueous solutions, by adsorption on activated carbon prepared from rice hulls (ACRH); was investigated depending on pH, activated carbon dosage, contact time, initial metal concentration and solution temperature. The optimum values of pH, ACRH dosage and contact time were determined to be 5-8, 0.5 g ACRH/25 mt solution an 60 minutes respectively for the adsorption of Cu (II) ions and 5-8, 1.5 g ACRH/25 mt solution and 60 minutes for the adsorption of Cd (II) ions. From the initial concentrations, the constants for the Freundlich and Langmuir isotherm were calculated at 293 K and 313 K. The adsorption of Cu (II) and Cd (II) ions from aqueous solutions was found to be exothermic [Delta H degrees=-13.474 KJ/mol for Cu (II) and Delta H degrees=-2.302 KJ/mol for Cd (II)]. Furthermore, the other thermodynamic data for Delta G degrees and Delta S degrees, were also calculated at 293 K and 313 K.
Keywords: adsorption; heavy metal; activated carbon; rice hulls; FLY-ASH; Chemistry; Engineering